Android Application Permissions and Privacy Issues - Philip, Jithu; Raju, Merin (Indian Journal of Computer Science, 2023)
The use of smartphones increased worldwide during the past decade. The usage share of mobile Operating Systems shows the popularity and acceptability of mobile Operating Systems along with its application programs. Android remains the most widely used mobile operating system in the world. Here in this paper we discuss about the workflow of Android applications along with the application permissions and privacy issues related to it.